STRATEGI BANK INDONESIA PROVINSI BALI DALAM EDUKASI MELALUI JINGLE CBP RUPIAH BERDASARKAN DIGITAL MINDSET - Sujata, I Nyoman Ganes Ari; Ramayu, I Made Satrya; Heptariza, Anita (Universitas Dharmawangsa, 2025)
This study explores the strategy of Bank Indonesia Bali Province in educating the public about the values of Cinta, Bangga, Paham, Rupiah (CBP) Rupiah throught a jingle using a digital mindset approach. The CBP Rupiah Progra, aims to raise public awareness about the importance of Rupiah as a national symbol and legal tender. A qualitative descriptive method was employed, using interviews, observation, and documentation as data collection techniques. The findings show that the jingle is effective as an educational tool due to its simple and memorable lyrics. The use of digital platfrom such as Youtube and Instagram has significantly expanded the program’s reach. The combination of educational messages with digital dissemination helps improve public understanding, especially among younger audiences. This strategy is considered adaptive to technological trends and media consumption habits, and it can serve as an innovative model for public education initiatives in governmental intstitutions.